(3ehVhYGJ aj GdEMUGA GdGLJeGYj hefgL GdHMK GdYdej (B/s - (3cQGOTI, efjQ YHO Gddg SdeGfs ((3YeGf, GdCQOf (B:s (3OGQ CeLO ddfTQ hGdJhRjY,s (3EHUGQ fGTQhf hehRYhf GdeMJQahf GdCQOfjhf dUfGYI HQGjd (B:s (3OGQ caGAI GdeYQaI WHGYI(B. (3fTQ(B. (3JhRjY,s, 2022)
(3JHQR CgejI Yde GdEMUGA aj eG jbOeg ef eSGgeI YedjI GJNGP GdbQGQGJ Mhd XhGgQ Ch bVGjG eMOOI, MjK jecf Yf WQjb gPG GdYde GdJhUd Edi GdMbGFb GdJj JTcd GdCSGS GdVQhQj aj GJNGP GdKQGQGJ GdYbdGfjI GdQTjOI, hage GdXhGgQ GdeQZhHI OQGSJgG, hage GdYhGed GdeDKQI ajgG hGQJHGWGJgG hJMOjO CjVG GfYcGSGJgG GdeNJdaI hHGdJGdj JbOje age Yejb hObjb Mhd GdXGgQI bjO GdOQGSI hGdYhGed GdedGReI hGdeaSQI dgG(B.s
(3HHdjhLQGajI (B: (3UaMI (B275-276.s
Keywords: (3GdYdhe GdGLJeGYjIs -- (3CSGdjH EMUGFjIs; (3WQb GdHMKs; (3GdEfSGfjGJs -- (3CSGdjH EMUGFjIs